2003
DOI: 10.1097/00005537-200308000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans of the Head and Neck: Treatment With Mohs Surgery Using Inverted Horizontal Paraffin Sections

Abstract: Dermatofibrosarcoma protuberans of the head and neck is a tumor that shows extensive infiltration beyond gross margins. Wide local excision with 2- to 3-cm margins results in an unacceptably high recurrence rate; larger excisional margins are necessary to remove all disease. Accurate margin identification achieved by using Mohs surgery with rush paraffin section analysis results in complete tumor removal and excellent control rates. This method should be preferred for treatment of dermatofibrosarcoma protubera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…This approach has been corroborated by reports of DFSP studied simultaneously using paraffin and frozen sections. [21][22][23] The limitations of using paraffin sections are that they are time-consuming to process with the consequent discomfort from open wounds between stages. In our series, we have obtained very good results, achieving a 0% recurrence rate with mean followup of 68 months.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been corroborated by reports of DFSP studied simultaneously using paraffin and frozen sections. [21][22][23] The limitations of using paraffin sections are that they are time-consuming to process with the consequent discomfort from open wounds between stages. In our series, we have obtained very good results, achieving a 0% recurrence rate with mean followup of 68 months.…”
Section: Discussionmentioning
confidence: 99%
“…Tom and colleagues reported that accurate margin identification achieved by using Mohs' micrographic surgery with rush paraffin section analysis results in complete tumor removal and excellent control rates 21 . The authors suggest that this method should be preferred for treatment of DFSP of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Supporters of MMS believe that with the complete threedimensional histological examination on paraYn sections, enhanced by immunohistochemical (anti-CD34) margin control (Jimenez et al 1994), it is an optimal therapy option in margin assessment of DFSP (Robinson 1985;Gloster et al 1996;Haycox et al 1997b;Ratner et al 1997;AhWeng et al 2002;Nouri et al 2002;Tom et al 2003;DuBay et al 2004;Snow et al 2004;Wacker et al 2004;Thornton et al 2005). They recommend the use of MMS especially in recurrent disease and widespread, asymmetric tumor formations.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%